Seismic Design and Evaluation of Elevated Steel Tanks Supported by Concentric Braced Frames - Roberto Nascimbene; Gian Andrea Rassati (CivilEng, 2024)
The current investigation delved into the seismic analysis, design intricacies, and assessment of the response of elevated steel containment tanks when supported by concentrically braced frames. The primary focus was placed on comprehending the behavior of the supporting structure, recognizing its heightened vulnerability to damage under horizontal excitation—insights gleaned from reconnaissance teams studying earthquake aftermaths worldwide. A specific case study unfolded featuring a steel concentrically braced frame as the supporting structure, aligning with prevalent industry norms. Throughout the entire process, spanning design phases, seismic vulnerability assessments, and response evaluations, special emphasis was placed on the internal fluid sloshing phenomena. This nuanced consideration plays a pivotal role in shaping the dynamic response of the system. The study introduces two distinct design methods: the first method aligns with relevant international codes, while the second method innovatively incorporates the compressive strength of the braces into its approach. To evaluate the dynamic response of the elevated tank, both linear and nonlinear advanced analyses were employed. The comparative analysis of various strategies underscores the impact of the chosen design methodology on the overall system response. This multifaceted exploration aims to contribute valuable insights to the seismic resilience and design optimization of elevated steel containment tanks, furthering the understanding of their performance under seismic forces.